Decoupling – shifts in ecological footprint intensity of nations in the last decade. (January 2017) - Szigeti, Cecilia; Toth, Gergely; Szabo, Daniel Robert
Highlights: Richard York, Eugene A. Rosa and Thomas Dietz published the eco-footprint intensity of nations in 2004, as a one-time „snapshot". We added the time dimension, with a 10 years' revision. We found interesting results, seemingly against the Jevons-paradox. This could also be understood as putting a figure on the so-called T (technology) factor from the IPAT formula, the ratio of GDP and the ecological footprint. Results make us optimistic: 30% of countries showed strong, 59% weak decoupling and only 11% bad tendencies. But caution: the overall growth and overvaluation of GDP distort the results – sustainability is not yet achieved! Abstract: The ecological price of economic growth is a heavily debated issue, where ideologies often neglect factual information. In this paper, through the relationship of the ecological footprint and GDP, we examine the tendencies of eco-efficiency in the first decade of the 21st century. We conclude that the average ecological footprint intensity of countries have improved significantly in the given period. In 2009, 50 percent less area was needed to produce a unit of GDP. Many countries could reach the so-called strong decoupling − these countries could increase GDP while decreasing the ecological footprint in absolute terms. We also repeated the analysis of a scientific article published in 2004. We managed to update data and identify ecologically positive tendencies. In ten years, the average of the world's ecological footprint intensity has significantly improved, it halved all in all. We found that 90 percent of the countries started to move to the direction of sustainable development. Among the studied 131 countries, 40 experienced strong decoupling (absolute decrease of resource use), in 77 countries weak decoupling occurred (relative decrease of resource use), and there were only 14 countries, where no decoupling could be observed (relative increase of resource use).